2022
DOI: 10.1111/1744-7917.13158
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral function of peptidoglycan recognition protein in Spodoptera exigua (Lepidoptera: Noctuidae)

Abstract: Peptidoglycan recognition proteins (PGRPs) are a class of molecules that play a critical role in insect immunity. Understanding the function of PGRPs is important to improve the efficiency of microbial insecticides. In this study, we investigated the role of PGRP-LB (a long type PGRP) in insect immunity against viruses using Spodoptera exigua and Spodoptera exigua multiple nucleopolyhedrovirus (SeMNPV) as an insectvirus model. We cloned and identified a PGRP-LB gene from S. exigua; the gene consisted of 7 exon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…In our study, we observed half of target DEmRNAs targeted by DElncRNAs were enriched in catabolic and metabolism; meanwhile, KEGG pathway analysis also showed that target genes of DElncRNAs were enriched in immune response and metabolism, suggesting that lncRNAs induced by BmBDV may regulate catabolic metabolism and affect BmBDV replication. What's more, recent studies suggest that Cysteine‐Rich with EGF‐like Domains 2 (CRELD2, BMSK0015577) is associated with pathological conditions involving endoplasmic reticulum stress, an important defense mechanism in the animal organism (Tang et al, 2023); Peptidoglycan recognition proteins (PGRPs) are a class of molecules that play a critical role in insect immunity, PGRP‐LB (BMSK0009347) has been shown strong antiviral effect against SeMNPV in Spodoptera exigua (Li, Li, et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we observed half of target DEmRNAs targeted by DElncRNAs were enriched in catabolic and metabolism; meanwhile, KEGG pathway analysis also showed that target genes of DElncRNAs were enriched in immune response and metabolism, suggesting that lncRNAs induced by BmBDV may regulate catabolic metabolism and affect BmBDV replication. What's more, recent studies suggest that Cysteine‐Rich with EGF‐like Domains 2 (CRELD2, BMSK0015577) is associated with pathological conditions involving endoplasmic reticulum stress, an important defense mechanism in the animal organism (Tang et al, 2023); Peptidoglycan recognition proteins (PGRPs) are a class of molecules that play a critical role in insect immunity, PGRP‐LB (BMSK0009347) has been shown strong antiviral effect against SeMNPV in Spodoptera exigua (Li, Li, et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…(51,190) iii. Signal conduction (53,93,191,192) iv. Bacteriostasis or sterilization (74,193) Agglutination ( 96…”
Section: Discussionmentioning
confidence: 99%